Ethical awareness amongst engineering students in Malaysian public universities - Md. Som, Hishamuddin; Johari, Mohd. Janib; Nordin, Shaharom; Daud, Muhammad; Ahmad, Mohd. Fuad; Md. Yusoff, Rosman; Kunju Pillai Laxman, Lekha; Thukiman, Kassim; Abdul Ghani, Mohamad Pauzi; Low, Hock Heng; Abu, Baharin; Md. Ali, Azlah; et al. (Faculty of Management and Human Resource Development, 2005)
The area of ethics has received increased attention from the private and public sectors as well as academics over the past several decades. In the West, the highly publicized incidents at Enron and Arthur Anderson as well as WorldCom have brought the topic of ethics particularly business ethics to the public’s attention. There have been a multitude of scandals in the government, business and other areas of national life which includes the unethical conduct of top executives on Wall Street related to insider trading, the suspected misuse of research grants at Stanford University and a few other incidents captured by the media. In Malaysia, two general managers of the National Pilgrimage Board (LTH) had been charged in court for breach of trust by withholding information that could affect the decision not to invest RM400 million in foreign exchange activities (The New Straits Times, 15 February, 2003). The Malaysian government was also aware that one of the reasons for the failure of some government-linked companies was due to dishonest officers (The New Straits Times, 25 August, 2005).